Customers’ satisfaction towards Penang International Airport Services / Nasirah Saidin, Nazatul Nadhirah Nazarudin and Wan Nursyahidatul Husna Mohd Noor - Saidin, Nasirah; Nazarudin, Nazatul Nadhirah; Mohd Noor, Wan Nursyahidatul Husna (2016)
This study conduct to know the factors (tangible, reliability, responsiveness, assurance and empathy) that affecting the customers’ satisfaction towards Penang International Airport service. Sample size of this study was 384 passengers in Penang International Airport by using Simple Random Sampling. The data was collected online through Google Drive with a self-administered questionnaire and it was analyzed using independent t-test and multiple linear regression. From this study, researcher know that between local and foreigner passenger, there were statistically significant difference of satisfaction of airport services. Tangible, Assurance and Empathy were found to have a significant influence on the Customers’ Satisfaction towards Penang International Airport. The findings of this study will help airport administrators to identify important factors that affecting the customers’ satisfaction in the airport